2019
DOI: 10.1093/jtm/taz035
|View full text |Cite
|
Sign up to set email alerts
|

Seroprotection rates of vaccine-preventable diseases among newly arrived Eritrean asylum seekers in Switzerland: a cross-sectional study

Abstract: Background According to 2016 World Health Organization and United Nations Children’s Fund country estimates, Eritrea has overall high vaccination coverage with immunization rates for three doses of diphtheria/tetanus/pertussis and polio vaccine of 95%, for two doses measles vaccine of 85% and for three doses hepatitis B vaccine of 85%. If confirmed, this could imply that routine basic vaccination of newly arrived Eritreans could be safely omitted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Two studies from Central Europe with different refugee populations found lower immunity; a study on Eritrean refugees in Switzerland found 76.2% to be immune [23] and a study from Luxembourg from 2012 primarily involving refugees from Balkan found 73% to be immune [24] The low immunity in refugees from Balkan was also found in a study from Sweden, where only 68 % of immigrants/refugees from the former Yugoslavia and Albania were immune. [25].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Two studies from Central Europe with different refugee populations found lower immunity; a study on Eritrean refugees in Switzerland found 76.2% to be immune [23] and a study from Luxembourg from 2012 primarily involving refugees from Balkan found 73% to be immune [24] The low immunity in refugees from Balkan was also found in a study from Sweden, where only 68 % of immigrants/refugees from the former Yugoslavia and Albania were immune. [25].…”
Section: Discussionmentioning
confidence: 85%
“…Recent surveys from other European countries have found that measles immunity among adult asylum seekers was relatively high with seroprevalences ranging between 73 and92.6%, although not sufficient to reach herd immunity,. [19][20][21][22][23][24][25]. Only one of these studies involved seroprevalence results from Scandinavia and this study included adults only [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although Europe has seen a huge influx of migrants from low-to middle-income countries [12] and such migrants usually have a lower seroprotection for all vaccine preventable diseases including measles [13,14], our findings underpin that migrants are not the main drivers for measles resurgence in Europe. The number of migrants is possibly too low to account for such resurgence and is far surpassed by the number of international tourist arrivals.…”
Section: Discussionmentioning
confidence: 64%
“…With the increasing number of migrants to Europe from countries where measles virus is potentially circulating [12], there is concern that such migration could contribute to the measles resurgence in this region. Indeed, measles seroprotection in migrants is often suboptimal [13][14][15]. Measles outbreaks in migrant populations have been reported [16].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, displaced populations may not have benefited from universal vaccination programs, as has been documented in Rohingya refugees 26 . Several studies from European countries receiving refugees and asylum seekers show that seroprevalence of vaccine‐preventable diseases in these populations or subgroup populations do not meet levels required to confer herd immunity 27‐30 . When displaced populations with varying levels of immunization come together along migration routes and into crowded camps, highly contagious vaccine‐preventable diseases like measles (Figure 1) and varicella (Figure 2) can spread very quickly.…”
Section: Skin Diseases Associated With Suboptimal Infrastructurementioning
confidence: 99%